2019
DOI: 10.2147/cmar.s195324
|View full text |Cite
|
Sign up to set email alerts
|

<p>Combination of the preoperative albumin to globulin ratio and neutrophil to lymphocyte ratio as a novel prognostic factor in patients with triple negative breast cancer</p>

Abstract: Background: The pretreatment albumin to globulin ratio (AGR) and neutrophil to lymphocyte ratio (NLR) were the inflammation-associated factors which were related to the disease-free survival in various malignancies. The aim of this study was to evaluate the clinical significance of the pretreatment AGR combined with NLR for patients with triple negative breast cancer (TNBC). Method: This retrospective study included 286 cases of pathologically diagnosed patients with TNBC. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
(30 reference statements)
1
18
0
Order By: Relevance
“…Liu et al reported that inflammatory and nutritional markers were independent predictive indexes for the survival of gastric cancer patients (14). Combined indexes of inflammation and nutrition, such as PNI (18,32), SIS (22,33), and AGR (16,34) have been proved to be related to survival in cancers. Consistently, our study suggested that low level of PNI and AGR and high level of SIS had poor OS and DFS in NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al reported that inflammatory and nutritional markers were independent predictive indexes for the survival of gastric cancer patients (14). Combined indexes of inflammation and nutrition, such as PNI (18,32), SIS (22,33), and AGR (16,34) have been proved to be related to survival in cancers. Consistently, our study suggested that low level of PNI and AGR and high level of SIS had poor OS and DFS in NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils could inhibit cytotoxic lymphocytes through the release of arginase, reactive oxygen species and nitric oxide. Lymphocyte counts indicate anti-tumor immunity [13]. A previous study con rmed that ganoderma spore powder inhibits the production of TNF-α and IL-6 preventing sustained immune response [32].…”
Section: Discussionmentioning
confidence: 98%
“…These analyses demonstrated that activated molecules are differentially associated with cytokine production following drug stimuli suggesting a high possibility for effective evaluation of overall immune status. [13,22], Kaplan-Meier univariate survival analysis of AGR and NLR detection in each group showed that AGR, as well as PFS were positively correlated amongst breast cancer and lung cancer patients (HR = 1.572, P = 0.038). NLR was shown to be negatively correlated with PFS (HR = 2.064, P = 0.042), as shown in Fig.…”
Section: Exploratory Analysis Of T Cell Subset Associations With Cytomentioning
confidence: 97%
See 1 more Smart Citation
“…Widmann et al first reported the correlation between the NLR and BC prognosis in 316 patients, and it was found that a higher NLR (≥3.3) before treatment was an adverse factor for both short-and long-term mortality (15). The majority of retrospective studies thereafter have drawn similar conclusions (16)(17)(18)(19), and the NLR was found to be consistent among different BC subtypes at baseline (20,21). However, a prospective substudy of GEICAM/9906, which comprised 1,246 patients, did not find any prognostic value of the NLR after adjustment for clinicopathological factors; in addition, a high NLR was independently associated with worse DFS in only highrisk patients (the hormone receptor-negative/HER2+ population and in patients with ≥3 lymph node metastases) (22).…”
Section: Prognostic Value Of the Neutrophil-to-lymphocyte Ratio (Nlr)mentioning
confidence: 96%